Successful Treatment of Massive Pulmonary Embolism With Catheter-Directed Thrombolysis in a Patient With Lymphocele: A Rare Cause of Thromboembolism. (September 2016) - Cincin, Altug; Bozbay, Mehmet; Oguz, Mustafa; Sahin, Anil; Tanidir, Yiloren; Mutlu, Bulent
Abstract : Pulmonary embolism is a frequent and mortal situation especially in high-risk patients. Although thrombolytics and anticoagulants are the main options in treatment, substantial portion of patients also have high bleeding risk. Therefore, new catheter-directed treatment strategies, such as ultrasound-assisted transcatheter thrombolysis, gain importance in treatment options for intermediate and high-risk patients. Here, we report a case of massive pulmonary embolism due to the iatrogenic lymphocele after a radical retropubic prostatectomy procedure. The usage of ultrasound-assisted transcatheter thrombolysis was successful in such a high-risk patient. Abstract : Supplemental Digital Content is Available in the Text.